Language learning methods and their differences - Geldiyeva Khursandoy (Peerian Journals Publishing, 2022)
There are several ways to learn a language today. Over time, various new and effective methods of language teaching are being discovered. Methods of language teaching also depend on the period and requirements. For example, in the past, language teaching was often based on grammar, that is, the theoretical grammatical part of the language was taught. They also prepare for a foreign language test for admission to higher education institutions. In the tests, questions were asked on foreign language grammar and entrants were prepared for grammar. Later, the shortcomings of this method became apparent: the student had only theoretical knowledge, could not speak the language he learned, could not express his opinion, could not use the new words he learned, failed to develop. writing or reading skills and can pronounce new words correctly. These shortcomings are not immediately apparent, meaning that no single method has been developed to teach them simultaneously. Besides. Over the years, various methods have been developed, their successes and shortcomings have been studied, and effective methods of language teaching have been formed day by day.
Keywords: language teaching; method; grammar; conversation